Oxidative enzymes activity in cowpea (Vigna unguiculata) seeds simultaneous effect of sowing dates, seed treatments and nutrient spray - DIGAMBER; JAKHAR, S S; SINGH, KULDEEP; KUMAR, RAHUL; SINGH, GAGANDEEP; SINGH, SULTAN; SAINI, KARAN SINGH; KUMAR, VIKASH (The Indian Journal of Agricultural Sciences, 2024)
Oxidative enzyme activity in plants is affected by innumerable direct as well as indirect ways. Sowing dates, nutrients in the form of foliar sprays and pre-seed treatments are the most common paths that can enhance the activity of oxidative enzymes in plants. The present field study was carried out during rainy (kharif ) seasons of 2019–20 and 2021–22 at the experimental field of Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to evaluate the seed quality and yield of cowpea [Vigna unguiculata (L.) Walp] affected by the date of sowing, foliar application and seed treatment. The experiment was laid out in split-split plot design (SSPD) having 3 sowing dates, viz. 30 March (S1); 30 May (S2); and 30 June (S3) and 3 different seed treatments along with control i.e. T0, Control (untreated seeds); T1, Captan @2 g/kg; T2, Vitavax @2 g/kg; and T3, Bavistin @2 g/kg, replicated thrice. Nutrient spray, viz. FS0, No spray; FS1, NPK (18:18:18) @2%; FS2, NPK (17:44:0)-Urea phosphate @2% and FS3, NPK (0:0:50)- Sulphate of potash @2% were also done at at 35–45 DAS (days after sowing) and 55–65 DAS. The results reported that delayed sowing time reduced the oxidative enzyme activity and thus affected the productivity of quality cowpea. Captan was observed to be the most efficient and preventive, seed treatment agent. Out of the three-nutrient spray NPK @18:18:18 resulted in the maximum oxidative enzyme activity. The best quality seeds having highest values of oxidative enzyme activity including Catalase, Peroxidase, Dehydrogenase and Superoxide Dismutase were harvested from captan treated seed of second sowing with two sprays of NPK (18:18:18).